European temporal trends in the use of lymph node dissection in patients with renal cancer. Issue 11 (November 2017) - Capitanio, U.; Stewart, G.D.; Larcher, A.; Ouzaid, I.; Akdogan, B.; Roscigno, M.; Marszalek, M.; Dell'Oglio, P.; Salagierski, M.; Volpe, A.; Mir, M.C.; Kriegmair, M.; et al.
Abstract: Background: The role of lymph node dissection (LND) in renal cell carcinoma (RCC) is still under debate. We aimed to assess the utilization rates of LND over time in Europe. Methods: A multi-institutional database of 13, 581 RCC patients who underwent radical nephrectomy (RN) or nephron sparing surgery (NSS) between 1988 and 2014 was created within an European consortium. We analysed temporal trends in the frequency of LND by using Joinpoint regression. Logistic regression models were used to identify predictors of LND. Results: Overall, 5114 patients (42.7%) underwent LND. Lymph node invasion was recorded in 566 cases (11% of LND patients) which represents 4.7% of the whole study cohort. A gradual decline in the use of LND started in the 1990s. After 2008 LND decreased significantly by 21.5% per year (95%CI −33.3 to −7.5, p < 0.01) until 2011 and stabilized thereafter (Annual Percentage Change 4.9%, 95%CI −3.4 to 13.8, p = 0.2). At multivariable analyses, patient age (OR 0.98, p < 0.0001), type of surgery (RN vs. NSS: OR 5.46, p < 0.0001), surgical approach (open vs. minimally invasive: OR 1.75, p < 0.0001), T stage (T2 vs. T1: OR 1.57; T3-4 vs. T1: OR 1.44, p < 0.0001), clinical tumour size (OR 1.14, p < 0.0001), and year of surgery (OR 0.95, p < 0.0001) were associated with higher probability of LND at nephrectomy. Conclusions: A trend towards lower LND was observed over time for RCC patients who underwent RN or NSS. LND is more frequently performed in younger patients, locally advanced diseases and in case of open surgery.